Pressure effect on the spin density wave transition in La_{2}PrNi_{2}O_{6.96} - Rustem Khasanov; Igor Plokhikh; Thomas J. Hicken; Hubertus Luetkens; Dariusz J. Gawryluk; Zurab Guguchia (Physical Review Research)
High-pressure studies reveal a stark contrast between the superconducting properties of double-layer Ruddlesden-Popper (RP) nickelates La_{2}PrNi_{2}O_{7} and La_{3}Ni_{2}O_{7}. While La_{2}PrNi_{2}O_{7} exhibits bulk superconductivity, La_{3}Ni_{2}O_{7} displays filamentary behavior, suggesting that superconductivity is confined to phase interfaces rather than the bulk. Since magnetism emerges near the superconducting phase, understanding its differences in La_{3}Ni_{2}O_{7} and La_{2}PrNi_{2}O_{7} is essential for clarifying their underlying electronic and magnetic properties. In this work we study the magnetic responce of La_{2}PrNi_{2}O_{6.96} under pressures up to 2.3 GPa using the muon-spin rotation/relaxation (μSR) technique. The application of external pressure increases the Néel temperature T_{N} from approximately 161 K at ambient pressure (p=0) to about 170 K at p=2.30GPa. The temperature dependence of the internal magnetic field B_{int}(T) (i.e., the magnetic order parameter) follows the power-law relation B_{int}=B_{int}(0)(1−[T/T_{N}]^{α})^{β}, with consistent exponent values of α≃1.95 and β≃0.35 across different pressures. The value of the ordered moments at the Ni sites, which is proportional to B_{int}, remain unaffected by pressure. Our findings suggest that the magnetic properties of double-layer RP nickelate La_{3}Ni_{2}O_{7} are broadly unaffected by Pr to La substitution. The slightly elevated Néel temperature for La_{2}PrNi_{2}O_{7} compared to La_{3}Ni_{2}O_{7} represents the most notable distinction, suggesting subtle effects arising from Pr substitution within the studied pressure range.